Asian countries go for green economy - Carteciano, Joselito A.
The article is a summary of the 12th Science Council of Asia (SCA) Conference held on July 12, 2012 at Bogor, Indonesia with the theme "Mobilizing Science Towards Green Economy" and participated by 16 Asia Pacific countries including the Philippines. One of the most significant event of the conference is the establishment of the Coalition for Green Economy.